Anticoagulation in atrial fibrillation. Issue 4 (April 2019) - Utomi, Victor; Draper, Richard
Atrial fibrillation is the most common sustained disturbance of cardiac rhythm. It is a global epidemic and an evolving problem in cardiovascular medicine. Atrial fibrillation is an independent risk factor for embolic stroke, increasing the risk of stroke five-fold. Despite good evidence for the reduction of stroke risk with anticoagulant therapy, there is significant under treatment. Anticoagulant prescribing is frequently discordant with all current guidelines and decision aids with both over and under use of oral anticoagulants. It is important that GPs have up-to-date knowledge about atrial fibrillation in terms of both its diagnosis and management, and that patients have an understanding of anticoagulant medication. This article aims to update knowledge about atrial fibrillation, the use and benefits of anticoagulation with insights on some barriers to anticoagulation in primary care. This article does not cover management of atrial fibrillation with control of cardiac rate or rhythm to maintain cardiac function.